2019
DOI: 10.1016/j.expneurol.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Excess glutamate secreted from astrocytes drives upregulation of P-glycoprotein in endothelial cells in amyotrophic lateral sclerosis

Abstract: In amyotrophic lateral sclerosis (ALS), upregulation in expression and activity of the ABC transporter P-glycoprotein (P-gp) driven by disease advancement progressively reduces CNS penetration and efficacy of the ALS drug, riluzole. Post-mortem spinal cord tissues from ALS patients revealed elevated P-gp expression levels in endothelial cells of the blood-spinal cord barrier compared to levels measured in control, non-diseased individuals. We recently found that astrocytes expressing familial ALS-linked SOD1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…We also found that heat stress could induce the expression of P-gp. As previously published, heat stress-induced some molecules, such as HIF-1α [21] and cyclooxygenase-2 (COX-2) [22], could induce the expression of P-gp. Notably, P-gp is known to play an important role in the efflux of various chemical mediators.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that heat stress could induce the expression of P-gp. As previously published, heat stress-induced some molecules, such as HIF-1α [21] and cyclooxygenase-2 (COX-2) [22], could induce the expression of P-gp. Notably, P-gp is known to play an important role in the efflux of various chemical mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Activated astrocytes release large amounts of glutamate that act on endothelial NMDA receptors and promote oxidative stress (Scott et al, 2007), TJ disruption, and increased BBB permeability (Andras et al, 2007). Further, glutamate increases the expression of P-gp, as reported in endothelial cells cultured with astrocytes derived from amyotrophic lateral sclerosis (ALS) patients (Mohamed et al, 2019). This condition can justify "P-gp–mediated pharmacoresistance" (Mohamed et al, 2017), often observed in diseases including ALS and epilepsy (Avemary et al, 2013; Feldmann et al, 2013).…”
Section: The Dual Role Of Astrocytic-derived Factors: From Endotheliamentioning
confidence: 73%
“…This is also important to consider in the case of riluzole, since it has been shown that although riluzole alone had no effect in SOD1 G93A mice, when combined with elacridar, a drug which inhibits transporters including P-glycoprotein that control drug efflux from the central nervous system, motor function was improved and survival was significantly extended (43). P-glycoprotein is up-regulated in ALS at least in part in response to astrocytic release of glutamate, and this upregulation may decrease penetration of riluzole into the central nervous system (44).…”
Section: Discussionmentioning
confidence: 99%